Sensoriamento remoto na identificação do uso e ocupação da terra na área do projeto Conquista da Água, Ilha Solteira - SP, Brasil - Silva, Helio Ricardo [UNESP]; Altimare, André L. [UNESP]; Lima, Elizete A. C. de Freitas [UNESP] (Associação Brasileira de Engenharia Agrícola (SBEA), 2006)
A cidade de Ilha Solteira está propondo o projeto Conquista da Água, visando ao desenvolvimento sustentável do Município, a partir do turismo, da cultura e da ciência e tecnologia. Para atingir esse objetivo, os planejadores do meio físico-ambiental necessitam de dados que possam auxiliá-los na seleção dos melhores locais onde serão instalados as avenidas, o aeroporto e os demais espaços que comporão esse projeto. A elaboração do mapa de uso e cobertura do solo da área de interesse do projeto constitui um dos temas necessários ao banco de dados a ser utilizado pelos planejadores. Neste trabalho, é apresentado o estado de degradação dessa área, o que auxiliará na definição das estratégias de conservação ambiental.

The City hall of Ilha Solteira is proposing the project Management of the Water, seeking to contribute with the sustainable development of the municipal district, through tourism, culture, science and technology. To reach it, the planners of the physical-environmental way, will need data that will aid in the selection of the best local to install the avenues, the airport and other spaces that will compose this project. The elaboration of a Map of the current use and cover of the lands in the area of interest of the project represents one of the necessary themes to compose a database to be used by the planners. In the present work, it is presented a discussion on the state of degradation of the landscape, which will help the definition of strategies of environmental conservation.
Remote sensing on the identification of the use and occupation of land of the project Management of the Water, Ilha Solteira - State of São Paulo, Brazil
Keywords: desenvolvimento sustentável; geoprocessamento; mapas; sustainable development; geoprocessing; maps